Wealth Inequality and Homeownership in Europe - Edgar Preugschat; Leo Kaas; Georgi Kocharkov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The nine largest countries in the Euro area have surprisingly different degrees of wealth inequality. At the same time, there is a strong negative correlation between wealth inequality and homeownership rates across countries. To account for this fact, we first analyze decompositions of the Gini coefficient across subgroups of households. The main contributing factor for the negative correlation with homeownership appears to be inequality between homeowners and renters. In a second step, we estimate the effects of homeownership on the Gini using a Recentered Influence Function (RIF) regression approach. The coefficients on homeownership are significantly negative and are positively correlated with between group Ginis (owners vs renters) across countries. To better understand the effect of ownership on inequality we regress ownership on individual quantiles. For most countries the effect of ownership is strongest for quantiles below the median. This suggests that policies promoting homeownership for lower wealth groups should have the largest impact wealth inequality.
Keywords: D31; E21; G11; 330